2016
DOI: 10.1002/cjce.22477
|View full text |Cite
|
Sign up to set email alerts
|

Role of binary solvent and ionic liquid in bitumen recovery from oil sands

Abstract: A binary solvent of ethyl acetate and n‐heptane was made and applied together with ionic liquids (ILs, 1‐ethyl‐3‐methyl imidazolium tetrafluoroborate ([Emim]BF4)) to extract bitumen from oil sands at ambient conditions. Results of bottle tests show that the bitumen recovery is highly dependent on the volume ratio of ethyl acetate to n‐heptane. The maximum recovery was obtained at the ethyl acetate‐to‐n‐heptane ratio of 3:6. With external addition of ILs, an additional improvement of ∼10 % of bitumen recovery w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 21 publications
2
26
0
Order By: Relevance
“…10 To improve this situation, great efforts have been made. [18][19][20][21][22] For example, Sui et al proposed the application of switchable solvent to recover the asphalt. They obtained a high asphalt recovery of 97% and the switchable solvent could be recovered easily.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…10 To improve this situation, great efforts have been made. [18][19][20][21][22] For example, Sui et al proposed the application of switchable solvent to recover the asphalt. They obtained a high asphalt recovery of 97% and the switchable solvent could be recovered easily.…”
Section: Introductionmentioning
confidence: 99%
“…The heavy hydrocarbons recovery was up to 93.04% and the solvent entrainment in the waste solids was highly inhibited. 20 They obtained excellent results, while these new methods were beyond applications at present due to high cost on both chemicals and operation. Some researchers believed that pyrolysis would be a potential way for the exploitation of the Indonesian asphalt rocks, 15,[23][24][25] because the asphalt could be directly cracked into light oil fractions or gases without adding external chemicals.…”
Section: Introductionmentioning
confidence: 99%
“…[Emim][BF4]) to enhance solvent extraction (Li et al, 2011;Sui et al, 2016;Tourvieille et al, 2017). Li et al (2011) reported the maximum bitumen recovery was 86% at the acetone-to-nheptane ratio of 2:…”
Section: Ionic Liquidmentioning
confidence: 99%
“…Since 92 % (by weight) bitumen recovery was obtained even when the IL was reused 10 times, the solvent extraction technology using composite solvent enhanced by IL was encouraged to be extended from bench scale to the oil sand industry by Li et al (2011). Sui et al (2016) examined the effect of operational parameters (i.e., IL-to-oil sands ratio, agitation time, and conditioning time) on bitumen recovery from oil sands using IL enhanced solvent extraction. It was found that bitumen recovery increased as IL-to-oil sands ratio and agitation time increased, whereas the conditioning time had a negligible effect on bitumen recovery.…”
Section: Ionic Liquidmentioning
confidence: 99%
See 1 more Smart Citation